Gibberellin-mediated internode elongation in grasses with a focus on bamboo: molecular pathways and regulatory networks - Dai, Lei; Zhao, Xiumin; Liu, Shiying; Keerthana, Krishnamurthi; Vijayakanth, Venkatesan; Zhi, Yongqi; Chen, Ming; Que, Feng; Ramakrishnan, Muthusamy; Ahmad, Zishan; Wei, Qiang (Frontiers in Plant Science, 2025)
Internode elongation in Poaceae plants significantly influences stem development and grain yield. Gibberellin (GA), a key hormone, regulates this elongation and overall development. In cereal members of Poaceae, such as rice and wheat, the application of dwarfing genes involved in GA metabolism or signaling pathways during the Green Revolution led to increased grain yield, underscoring GA’s importance in plant breeding. Although bamboo was not a part of this historical context, optimizing its growth requires an understanding of GA-mediated internode elongation control. This review systematically elucidates the molecular framework of GA-regulated internode elongation in Poaceae, with a specific focus on bamboo. It examines GA’s biosynthetic pathway, metabolic regulation, and signal transduction mechanisms. The review also discusses how GA interacts with other hormone pathways to regulate internode growth and suggests future research directions. Finally, this review provides a reference for a deeper understanding of the molecular mechanisms behind GA-regulated bamboo internode growth and its potential application in bamboo breeding.